Progress on the Photocatalytic Reduction Removal of Chromium Contamination - Zhao, Zengying; An, He; Lin, Jing; Feng, Mingchao; Murugadoss, Vignesh; Ding, Tao; Liu, Hu; Shao, Qian; Mai, Xianmin; Wang, Ning; Gu, Hongbo; Angaiah, Subramania; et al. (Chemical record, 2019)
Rapid industrialization leads to increased wastewater discharge encompassing hexavalent chromium (Cr(VI)), which leads to serious environmental problems of toxicity and potential carcinogenicity. Removal of these species is normally carried out by ion‐exchange, precipitation, membrane filtration, sorption, photocatalytic reduction, etc. This review mainly focuses on the photocatalytic and photoelectrocatalytic (PEC) reduction of Cr (VI), because of their advantages over other methods such as reduced risk of secondary pollution by non‐reduced Cr (VI), no sludge formation, no need for a large amount of chemical reagents, clean and easy installation. The main factors influencing the photocatalytic reduction efficiency of Cr (VI) such as catalyst activity, solution pH, Cr adsorption on the catalyst and additives, are briefly discussed. Finally, a special emphasis is provided to the photoelectrocatalytic (PEC) reduction of Cr (VI). An insight into the photocatalytic reduction of chromium ions in water treatment.